Comparative legal solution for rehabilitating legacy mines through financial provision in South Africa and Western Australia - F. Agyemang; J. C. N. Ashukem (The Southern African Institute of Mining and Metallurgy, 2025)
One understudied area of environmental law is the socio-ecological impact of ownerless mines. This impact is particularly pronounced in resource-dependent regions like South Africa and Western Australia, creating significant rehabilitation challenges. This article hypothesises that effectively managed financial provision could be valuable for rehabilitating legacy mines. Using a qualitative, comparative methodology, the article analyses the financial provisions for mine rehabilitation in South Africa and Western Australia, focusing on statutory provisions, funding mechanisms, and rehabilitation outcomes. Key themes, such as context, measures, and outcomes, are explored to assess the effectiveness of each financial model. Purposive sampling is used to select case studies from both regions, and thematic analysis is applied to interpret the data. The analysis highlights the financial rehabilitation measures in both regions, providing a structured framework for ownerless mine rehabilitation. South Africa's approach, guided by the Mineral and Petroleum Resources Development Act (MPRDA) of 2002, depends on state budget allocations, leading to funding inconsistencies and slow rehabilitation progress. In contrast, Western Australia’s Mine Rehabilitation Fund Act (MRFA) of 2012 uses a levy-based system, ensuring continuous financial support for mine rehabilitation. South Africa's state-dependent model has led to delays in rehabilitating derelict and ownerless mines, while Western Australia’s funding model has facilitated steady progress. The article recommends that South Africa adopt a levy-based financial mechanism, strengthen legislative enforcement, improve financial oversight, and integrate proactive mine closure strategies to accelerate rehabilitation, reduce environmental hazards, and promote sustainable development in mining-affected communities.